2020
DOI: 10.1089/ham.2020.0026
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Determinants of Acute Mountain Sickness in Mount Kinabalu, Malaysia

Abstract: Background: Acute mountain sickness (AMS) is the most common type of high-altitude sickness. The incidence of AMS varies by mountain location, trail characteristics, and study design. The lack of local epidemiology data has driven us to investigate the incidence and severity of AMS and its associated factors at Mount Kinabalu, Malaysia. Methods: A cohort study was conducted to collect data from climbers after days 1 (3272 m) and 2 (4095 m) of ascent. A self-administered questionnaire was used to explore climbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
5
2
4
Order By: Relevance
“…This was consistent with our findings. Previous studies have also shown that alcohol use and obesity are associated with AMS (San Martin et al, 2017;Yang et al, 2020), whereas we found no difference in BMI and alcohol history between the two groups. Notably, a meta-analysis showed smoking to be neither a risk nor a protective factor, whereas we found that smoking was protective against AMS.…”
Section: Potential Risk Factors For Amscontrasting
confidence: 79%
“…This was consistent with our findings. Previous studies have also shown that alcohol use and obesity are associated with AMS (San Martin et al, 2017;Yang et al, 2020), whereas we found no difference in BMI and alcohol history between the two groups. Notably, a meta-analysis showed smoking to be neither a risk nor a protective factor, whereas we found that smoking was protective against AMS.…”
Section: Potential Risk Factors For Amscontrasting
confidence: 79%
“…Rather, sleeping condition influenced the AMS. Study limitations should also be considered for the future studies, because LLS does not consider other effects, such as smoking [ 21 ] and alcohol intake [ 22 ], on the AMS risk.…”
Section: Discussionmentioning
confidence: 99%
“…Kejadian AMS dipengaruhi dengan ketinggian gunung yang didaki, kecepatan berjalan, lamanya tinggal atau istirahat pada ketinggian tersebut, serta derajat aklmatisasi (Yang et al, 2020). Salah satu risiko high-altitute illness yang berat menunjukkan Hypoxic Ventilator Response (HVR) yang berakibat terjadinya takipnea karena penurunan kadar oksigen secara tiba-tiba dan psikologis pada kondisi hipoksia dipengaruhi oleh karakteristik penderita AMS.…”
Section: Pembahasanunclassified